Early Detection Education for TB–HIV Among Mosque Congregants During the Ramadan Safari Program in the Jajag Primary Health Center Catchment Area, Banyuwangi - Byba Melda Suhita; Dora Ayu Prima Animo; Diah Fitrianingsih (FKM UIN Sumatera Utara Medan, 2026)
Low awareness of early detection has serious impacts. Individually, a delay in diagnosing TB can cause the disease to become severe and infect those closest to you, while HIV that is detected late will progress to the deadly AIDS stage.. One of them is in the community working area of the Jajag Health Center which is located in Gambiran District, Banyuwangi Regency. This community service activity aims to increase the congregation's knowledge and awareness regarding Tuberculosis (TB) and Human Immunodeficiency Virus (HIV), especially regarding early symptoms, transmission methods, and the importance of early detection, which is held during the fasting month through the Ramadhan Safari activity. This community service activity utilizes a community-based health education approach, implemented through a combination of outreach, participatory discussions, and voluntary screening services. The program successfully increased participants' knowledge of the symptoms, transmission, and importance of early detection of infectious diseases. The implementation of these activities also demonstrated that approaches through religious communities are effective in reaching communities that previously had limited access to health information. In addition to providing knowledge, these activities have begun to encourage changes in public attitudes toward health screening and foster collective awareness of the importance of disease prevention